Utilization of MG‐ADL in myasthenia gravis clinical research and care. Issue 6 (6th January 2022) - Muppidi, Srikanth; Silvestri, Nicholas J.; Tan, Robin; Riggs, Kimberly; Leighton, Trevor; Phillips, Glenn A.
Abstract: The Myasthenia Gravis Activities of Living (MG‐ADL) scale is an 8‐item patient‐reported scale that measures myasthenia gravis (MG) symptoms and functional status. The objective of the current review is to summarize the psychometric properties of the MG‐ADL and published evidence of MG‐ADL use. A targeted literature review for published studies of the MG‐ADL was conducted using a database and gray literature search. A total of 48 publications and 35 clinical trials were included. Studies indicated that the MG‐ADL is a reliable and valid measure that has been used as an outcome in clinical trials and observational studies to measure MG symptoms and response to treatment. While most often used as a secondary endpoint in clinical trials, its use as a primary endpoint has increased in recent years. The most common MG‐ADL endpoint is change in MG‐ADL score from baseline, although there has been an increase in the analysis of a responder threshold using the MG‐ADL. A new concept of minimal symptom expression (MSE) has emerged more recently. Duration of treatment effect is another important construct that is being increasingly evaluated using the MG‐ADL. The use of the MG‐ADL as a primary endpoint in clinical trials and in responder threshold analyses to indicate treatment improvement has increased in recent years. MSE using the MG‐ADL shows promise in helping to determine success of treatment and may be the aspirational goal of MG treatment for the future once validated, particularly given the evolving treatment landscape in MG.